NEUROPSYCHOLOGICAL INFLUENCE OF COLOR SOLUTIONS IN NAIL DESIGN ON THE EMOTIONAL STATE OF CLIENTS - Anel Barat (Modern American Journals, 2025)
This article examines the neuropsychological impact of color schemes in nail design on clients' emotional states. It examines the psychological and neuropsychological mechanisms of color perception, as well as the impact of different shades on mood, self-perception, and social perception. Particular attention is given to practical recommendations for nail technicians and brands on how to use color psychology to improve client satisfaction and foster a positive image. The analysis demonstrates that conscious color choices can have a significant impact on clients' emotional states and behavior, helping to improve their mood, confidence, and self-image.
Keywords: Neuropsychology, psychology of color, nail design, emotional state, manicure, color perception, emotional regulation, psychology of perception, customer experience, design and emotions.